Semi-sintered silver paste and its preparation method and application
The semi-sintered silver glue designed with specific components solves the problems of easy chip fall off and low reliability, and achieves the effects of high thermal conductivity, high temperature adhesive force and high residual glue rate, which is suitable for high-power chip mounting.
Patent Information
- Application Number
- CN202510089252.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing semi-sintered silver glue is prone to falling off in the reflow soldering process and has low reliability, especially in extreme environments to show serious losses in thermal conductivity and bonding strength.
Through the design of specific content components, including epoxy resin, epoxy diluent, resin composition, curing agent, coupling agent, inert solvent and silver powder, semi-sintered silver glue with high thermal conductivity, high high temperature adhesive strength and high residual glue rate are formed. This component works synergistically to form a strong bonding force between the chip and the substrate, improving the connection stability of the chip.
The stable connection of the chip in harsh environments is achieved, the risk of chip falling off due to stress is reduced, and the thermal conductivity and reliability of semi-sintered silver glue is significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic materials, and in particular relates to a semi-sintered silver paste and a preparation method and application thereof. Background Art
[0002] With the rapid rise of wide bandgap semiconductor materials represented by silicon carbide (SiC) and gallium nitride (GaN) in the power electronics industry, the application of high-power chips is increasing. For example, key components such as the main drive inverter, charging piles and on-board chargers of new energy vehicles all require high-power chips. These high-power chips generate a lot of heat when working, and have extremely high requirements for the thermal conductivity and reliability of the packaging materials. The excellent characteristics of semi-sintered silver glue can well meet these requirements and can quickly conduct the heat generated by the chip to avoid damage to the chip due to overheating. In addition, modern electronic devices are constantly developing towards miniaturization and high performance, and the requirements for chip integration and heat dissipation are getting higher and higher. Semi-sintered silver glue can achieve efficient heat dissipation and reliable connection in a smaller space, which is in line with the development trend of electronic equipment and promotes its application in high-power chip mounting.
[0003] The main components of semi-sintered silver paste include silver powder and other materials with good thermal conductivity. Compared with ordinary conductive paste, its thermal conductivity is greatly improved, which can meet the high requirements of high-power chips for heat dissipation, help maintain the stable operating temperature of the chip, and extend the service life of the chip. In addition, high-power chips are subject to various stresses during operation, such as thermal stress, mechanical stress, etc., so the mounting material needs to have a high bonding strength to ensure a firm connection of the chip.
[0004] However, the reliability of thermal conductive die-bonding adhesives in the prior art is insufficient, which is manifested in problems such as voids, cracks in the adhesive layer, and serious degradation of the die-bonding adhesive performance when bonding the chip to the base in extreme environments such as thermal shock, humidity, and heat. For example, the presence of voids causes a serious loss of thermal conductivity and bonding strength of the mounting material.
[0005] CN118480322A discloses a high thermal conductivity semi-sintered silver paste and its preparation method and application. The technical solution includes 85-90 parts of mixed silver powder (specific proportions of nanometer, submicron and micron spherical silver powder), 2-4 parts of epoxy resin, 0.5-2 parts of initiator, 0.5-1 parts of coupling agent and 5-8 parts of organic solvent, which solves the problems of poor heat dissipation function of existing semi-sintered silver materials and difficulty in effective volatilization of liquid phase when used for large-area sintering, but does not solve the problem of insufficient reliability of semi-sintered silver paste.
[0006] CN116313223A discloses a method for preparing silver paste, which can realize the preparation of high-solid content silver paste with high thermal conductivity and high sintering activity by using modified micron-sized silver powder and organic system. At the same time, the method avoids the agglomeration phenomenon caused by the use of nano silver powder, and can realize the uniform dispersion of ultra-high silver content silver paste. However, it does not solve the problem that the chip is easy to fall off and the reliability of silver paste is not high.
[0007] In summary, how to solve the problem of easy chip falling off and low reliability in the reflow soldering process has become a technical problem that needs to be solved urgently by technicians in the field of high-power chip mounting. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a semi-sintered silver paste and a preparation method and application thereof. Components with specific contents are adopted to achieve better overall interaction. The prepared semi-sintered silver paste has the characteristics of high thermal conductivity, high high-temperature adhesion and high residual glue rate, which solves the problem of easy chip falling off and low reliability in the reflow soldering process, and is suitable for the field of high-power chip mounting conductive silver paste.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a semi-sintered silver paste. The raw materials for preparing the semi-sintered silver paste include the following components in parts by weight: 35-55 parts of epoxy resin, 20-35 parts of epoxy diluent, 20-40 parts of resin composition, 1-4 parts of curing agent, 0.2-2 parts of coupling agent, 20-50 parts of inert solvent, and 800-900 parts of silver powder.
[0011] Among them, the epoxy resin can be 35 parts, 40 parts, 45 parts, 50 parts or 55 parts, etc.
[0012] Among them, the epoxy diluent can be 20 parts, 22 parts, 25 parts, 27 parts, 30 parts, 32 parts or 35 parts, etc.
[0013] The resin composition may be 20 parts, 25 parts, 30 parts, 35 parts or 40 parts, etc.
[0014] Among them, the curing agent can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts, etc.
[0015] The coupling agent may be 0.2 parts, 0.5 parts, 1 part, 1.5 parts or 2 parts.
[0016] The inert solvent may be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, etc.
[0017] Among them, the silver powder can be 800 parts, 810 parts, 820 parts, 830 parts, 840 parts, 850 parts, 860 parts, 870 parts, 880 parts, 890 parts or 900 parts, etc.
[0018] The epoxy diluent contains at least one epoxy group and at least one vinyl group.
[0019] The resin composition includes phenolic resin (PR), bismaleimide (BMI) and cyanate ester resin (CE).
[0020] The mass ratio of the phenolic resin, bismaleimide and cyanate resin is 1:(1-2):(1.5-3), wherein "1-2" can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2; "1.5-3" can be 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.
[0021] In the semi-sintered silver paste provided by the present invention, the epoxy resin, the epoxy diluent and the resin composition have a synergistic effect, which can form a strong bonding force between the chip and the substrate, so that the chip can maintain a stable connection under various harsh working conditions, and the risk of the chip falling off due to stress is reduced.
[0022] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0023] Preferably, the epoxy resin comprises a cycloaliphatic epoxy resin.
[0024] Preferably, the alicyclic epoxy resin contains at least 2 epoxy groups.
[0025] Preferably, the epoxy equivalent of the alicyclic epoxy resin is 100-190 g / Eq, for example, it can be 100 g / Eq, 110 g / Eq, 120 g / Eq, 130 g / Eq, 140 g / Eq, 150 g / Eq, 160 g / Eq, 170 g / Eq, 180 g / Eq or 190 g / Eq, etc.
[0026] The preferred technical solution of the present invention adopts alicyclic epoxy resin with a specific epoxy equivalent, so that the prepared semi-sintered silver paste has excellent heat resistance and processability.
[0027] Preferably, the epoxy diluent comprises 1,2-epoxy-4-vinylcyclohexane and / or 3,4-epoxycyclohexyl methacrylate.
[0028] Preferably, the hydroxyl equivalent of the phenolic resin is 198-230 g / Eq, for example, 198 g / Eq, 200 g / Eq, 210 g / Eq, 220 g / Eq or 230 g / Eq.
[0029] Preferably, the curing agent includes an imidazole curing agent and / or an epoxy curing agent.
[0030] Preferably, the coupling agent comprises a silane coupling agent.
[0031] Preferably, the inert solvent includes one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate or terpineol, or a combination of at least two of them.
[0032] Preferably, the silver powder is a combination of spherical silver powder and flaky silver powder.
[0033] Preferably, the mass ratio of spherical silver powder to flaky silver powder in the composition is 1:(2-4), for example, it can be 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.
[0034] The preferred technical solution of the present invention significantly improves the thermal conductivity of the semi-sintered silver paste by adding a combination of spherical silver powder and flaky silver powder. The combination of spherical silver powder and flaky silver powder increases the contact area, improves the density of the colloidal network, fills the gaps, and optimizes the morphology and particle size.
[0035] In a second aspect, the present invention provides a method for preparing the semi-sintered silver paste as described in the first aspect, the preparation method comprising the following steps:
[0036] (1) mixing the epoxy resin and the resin composition, heating and dissolving them, adding the epoxy diluent, curing agent and coupling agent, and stirring them evenly to obtain a resin mother solution;
[0037] (2) adding an inert solvent and silver powder to the resin mother solution obtained in step (1), mixing them evenly, and degassing them under a vacuum environment to obtain the semi-sintered silver paste.
[0038] The temperature for heating and dissolving is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C.
[0039] The vacuum degree of the vacuum environment is ≤-0.095 MPa, for example, it may be -0.1 MPa, -0.015 MPa, -0.2 MPa, -0.25 MPa or -0.3 MPa.
[0040] The degassing time is 10-25 min, for example, 10 min, 15 min, 17 min, 20 min, 22 min or 25 min.
[0041] In a third aspect, the present invention provides an application of the semi-sintered silver paste as described in the first aspect in packaging of high-power electronic devices.
[0042] Compared with the prior art, the present invention has at least the following beneficial effects:
[0043] (1) The present invention improves the high temperature resistance and interface bonding ability of the conductive adhesive by using a specific ratio of phenolic resin, bismaleimide and cyanate resin, so that the epoxy adhesive has both excellent operating performance and high reliability.
[0044] (2) The present invention improves the viscosity and rheological properties of the adhesive by adding an epoxy diluent. At the same time, the epoxy group in the epoxy diluent can react with the phenolic resin in the resin composition, and the vinyl group in the epoxy diluent can react with the bismaleimide in the resin composition to form a stable cross-linked structure, which effectively solves the problem of easy chip detachment and low reliability in the reflow soldering process.
[0045] (3) The semi-sintered silver paste provided by the present invention has good process operability and can better fill the gap between the chip and the substrate during the dispensing and curing process to form a uniform glue layer, reduce the generation of voids, and improve the quality and reliability of chip mounting. DETAILED DESCRIPTION
[0046] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0047] The sources of raw materials used in the following examples and comparative examples are as follows:
[0048] 1. Epoxy resin, TTA21P, purchased from Jiangsu Taitel New Materials Co., Ltd.;
[0049] 2. Epoxy resin, TTA800, purchased from Jiangsu Taitel New Materials Co., Ltd.;
[0050] 3. Epoxy resin, TTA28, purchased from Jiangsu Taitel New Materials Co., Ltd.;
[0051] 4. Epoxy diluent, TTA11, purchased from Jiangsu Taitel New Materials Co., Ltd.;
[0052] 5. Epoxy diluent, TTA15, purchased from Jiangsu Taitel New Materials Co., Ltd.;
[0053] 6. Epoxy diluent, ZL-622U, purchased from Xi'an Zhilun New Materials Company;
[0054] 7. Phenolic resin, SH-5065, purchased from Shandong Shengquan New Materials Company;
[0055] 8. Phenolic resin, SH-5075, purchased from Shandong Shengquan New Materials Company;
[0056] 9. Phenolic resin, SH-5085, purchased from Shandong Shengquan New Materials Company;
[0057] 10. Bismaleimide, PFB401, purchased from Shandong Shengquan New Materials Company;
[0058] 11. Bismaleimide, PFB301, purchased from Shandong Shengquan New Materials Company;
[0059] 12. Bismaleimide, PFB201, purchased from Shandong Shengquan New Materials Company;
[0060] 13. Cyanate resin, AroCy L-10, purchased from Huntsman, USA;
[0061] 14. Cyanate resin, C05C0100, purchased from Yangzhou Tianqi New Materials Company;
[0062] 15. Cyanate resin, C05C0400, purchased from Yangzhou Tianqi New Materials Company;
[0063] 16. Curing agent, 2E4MZ-CN, purchased from Shikoku Chemical Co., Ltd., Japan;
[0064] 17. Curing agent, 2E4MZ, purchased from Shikoku Chemical Co., Ltd., Japan;
[0065] 18. Curing agent, PN-50, purchased from Ajinomoto, Japan;
[0066] 19. Coupling agent, BYK4511, purchased from BYK Chemicals, Germany;
[0067] 20. Inert solvent, diethylene glycol butyl ether acetate, purchased from Hangzhou Bangyi Chemical Co., Ltd.;
[0068] 21. Flake silver powder, EA-0295PH, purchased from Metalor, USA, D50 = 6.0 μm;
[0069] 22. Spherical silver powder, KT071, purchased from Toyo Chemical Co., Ltd., Japan, D50 = 2.8 μm.
[0070] Example 1
[0071] A semi-sintered silver paste. The raw materials for preparing the semi-sintered silver paste include the following components by weight: 45 parts of epoxy resin (TTA21P), 27 parts of epoxy diluent (TTA11), 31 parts of resin composition, 2 parts of curing agent (2E4MZ-CN), 0.5 parts of coupling agent (BYK4511), 39 parts of inert solvent (butyl acetate of diethylene glycol), and 854 parts of silver powder.
[0072] The semi-sintered silver paste is prepared by the following method:
[0073] (1) After heating and dissolving 45 parts of epoxy resin, 7 parts of phenolic resin (SH-5065), 9 parts of bismaleimide (PFB401), and 15 parts of cyanate resin (AroCy L-10) at 90°C, 27 parts of epoxy diluent, 2 parts of curing agent, and 0.5 parts of coupling agent were added and stirred to obtain a resin mother solution;
[0074] (2) Add 39 parts of inert solvent, 640 parts of flaky silver powder (EA-0295PH) and 214 parts of spherical silver powder (KT071) to the resin mother liquor obtained in step (1), mix well and degas for 15 minutes at a vacuum degree of -0.095 MPa to obtain the semi-sintered silver paste.
[0075] Example 2
[0076] A semi-sintered silver paste. The raw materials for preparing the semi-sintered silver paste include the following components by weight: 55 parts of epoxy resin (TTA800), 35 parts of epoxy diluent (TTA15), 40 parts of resin composition, 4 parts of curing agent (2E4MZ), 2 parts of coupling agent (KH550), 50 parts of inert solvent (diethylene glycol butyl ether), and 900 parts of silver powder.
[0077] The semi-sintered silver paste is prepared by the following method:
[0078] (1) After heating and dissolving 55 parts of epoxy resin, 7 parts of phenolic resin (SH-5075), 14 parts of bismaleimide (PFB301), and 19 parts of cyanate resin (C05C0100) at 80°C, 35 parts of epoxy diluent, 4 parts of curing agent, and 5 parts of coupling agent were added and stirred to obtain a resin mother solution;
[0079] (2) Add 50 parts of an inert solvent, 720 parts of flaky silver powder (EA-0295PH) and 180 parts of spherical silver powder (KT071) to the resin mother liquor obtained in step (1), mix well and degas for 15 minutes at a vacuum degree of -0.095 MPa to obtain the semi-sintered silver paste.
[0080] Example 3
[0081] A semi-sintered silver paste. The raw materials for preparing the semi-sintered silver paste include the following components by weight: 35 parts of epoxy resin (TTA28), 20 parts of epoxy diluent (TTA11), 21 parts of resin composition, 1 part of curing agent (PN-50), 0.2 parts of coupling agent (KH570), 25 parts of inert solvent (pinene alcohol), and 800 parts of silver powder.
[0082] The semi-sintered silver paste is prepared by the following method:
[0083] (1) After heating and dissolving 35 parts of epoxy resin, 6 parts of phenolic resin (SH-5085), 6 parts of bismaleimide (PFB201), and 9 parts of cyanate resin (C05C0400) at 100°C, 20 parts of epoxy diluent, 1 part of curing agent, and 0.2 parts of coupling agent were added and stirred to obtain a resin mother solution;
[0084] (2) Add 25 parts of inert solvent, 540 parts of flaky silver powder (EA-0295PH) and 260 parts of spherical silver powder (KT071) to the resin mother liquor obtained in step (1), mix well and degas for 15 minutes at a vacuum degree of -0.095 MPa to obtain the semi-sintered silver paste.
[0085] Example 4
[0086] A semi-sintered silver paste, which is different from Example 1 in that: the high temperature resistant resin does not contain spherical silver powder, and the content of flaky silver powder is 854 parts.
[0087] Comparative Example 1
[0088] A semi-sintered silver paste, which is different from Example 1 in that: the high temperature resistant resin does not contain phenolic resin, and the content of bismaleimide is 16 parts.
[0089] Comparative Example 2
[0090] A semi-sintered silver paste, which is different from Example 1 in that: the high temperature resistant resin does not contain bismaleimide, and the content of phenolic resin is 16 parts.
[0091] Comparative Example 3
[0092] A semi-sintered silver paste, which is different from Example 1 in that: the high temperature resistant resin does not contain cyanate resin, the content of phenolic resin is 14 parts, and the content of bismaleimide is 17 parts.
[0093] Comparative Example 4
[0094] A semi-sintered silver paste, which is different from Example 1 in that an epoxy diluent (TTA11) in the raw materials for preparing the semi-sintered silver paste is replaced with an equal amount of epoxy diluent (ZL-622U).
[0095] Comparative Example 5
[0096] A semi-sintered silver paste, which is different from Example 1 in that: the raw materials for preparing the semi-sintered silver paste do not contain high temperature resistant resin.
[0097] Comparative Example 6
[0098] A semi-sintered silver paste. The raw materials for preparing the semi-sintered silver paste include the following components by weight: 60 parts of epoxy resin (TTA21P), 1.5 parts of curing agent (2E4MZ-CN), 0.5 parts of coupling agent (BYK4511), 26 parts of inert solvent (butyl acetate of diethylene glycol), and 854 parts of silver powder.
[0099] The semi-sintered silver paste is prepared by the following method:
[0100] (1) After heating and dissolving 45 parts of epoxy resin, add 2 parts of curing agent and 0.5 parts of coupling agent and stir evenly to obtain a resin mother solution;
[0101] (2) Add 39 parts of inert solvent, 640 parts of flaky silver powder (EA-0295PH) and 214 parts of spherical silver powder (KT071) to the resin mother liquor obtained in step (1), mix well and degas for 15 minutes at a vacuum degree of ≤-0.095 MPa to obtain the semi-sintered silver paste.
[0102] Test Method
[0103] Chip thrust: Die-Shear Strength test method refers to "HG / T 5912-2021 Conductive Adhesives", silicon wafer size: 2mm×2mm; substrate is silver-plated copper sheet, curing conditions are blast oven 175℃×1.0h; test equipment DAGE-4000P multi-function push-pull test machine, Nordson DAGE Precision Industries LTD, USA, shear strength is thrust size (unit is kgF); 10 samples of each glue, take the average value. When measuring 260℃ high temperature thrust, set the temperature of the temperature-controlled heating table, wait for the target temperature to reach and stabilize for 5 minutes, and then start measuring the thrust.
[0104] Evaluation of chip residual glue rate: Observe the residual glue on the substrate after thrust damage through an optical microscope, evaluate the area ratio of the residual glue part (percentage relative to the chip area), and take the arithmetic mean of 10 samples.
[0105] Evaluation of chip residual glue rate at 260℃: Observe the residual glue on the substrate after high-temperature thrust destruction at 260℃ through an optical microscope, evaluate the area ratio of the residual glue part (percentage relative to the chip area), and take the arithmetic mean of 10 samples.
[0106] Thermal conductivity: The test method refers to GB / T 22583-2008 and is tested using the LFA467 thermal conductivity meter from NETZSCH, Germany.
[0107] Test Results
[0108] The semi-sintered silver pastes provided in Examples 1-4 and Comparative Examples 1-6 were tested according to the above test method. The test results are shown in Table 1:
[0109] Table 1
[0110]
[0111] The test results show that:
[0112] (1) It can be seen from Examples 1 to 3 that the present invention achieves overall good interaction between the components by adopting specific component contents, and has the characteristics of high thermal conductivity, high high-temperature adhesion, and high residual adhesive rate.
[0113] (2) It can be seen from Examples 1 and 4 that the present invention further compounded spherical silver powder with flaky silver powder to make the silver powder particles more densely packed and more easily semi-sintered, thereby improving the thermal conductivity of the chip conductive adhesive.
[0114] (3) It can be seen from Example 1 and Comparative Example 1 that when the resin composition does not contain phenolic resin, the chip residual adhesive rate at room temperature and high temperature is significantly reduced, and the chip thrust is also sharply reduced at high temperature. This is because phenolic resin can not only improve the heat-resistant bonding performance of the conductive adhesive, but also has an important influence on the residual adhesive rate.
[0115] (4) It can be seen from Example 1 and Comparative Example 2 that when the resin composition does not contain bismaleimide, the normal temperature and high temperature thrust of the chip are significantly reduced. This is because bismaleimide plays an important role in improving the heat-resistant bonding performance of the conductive adhesive.
[0116] (5) It can be seen from Example 1 and Comparative Example 3 that when the resin composition does not contain cyanate ester resin, the normal temperature and high temperature thrust of the chip are significantly reduced, and the thermal conductivity is improved. This is because cyanate ester resin plays an important role in boosting the bonding performance of the conductive adhesive. At the same time, due to its unique dielectric properties, reducing its addition amount is beneficial to improving the thermal and electrical conductivity of the conductive adhesive.
[0117] (6) It can be seen from Example 1 and Comparative Example 4 that when the epoxy diluent in the formula is replaced with a difunctional epoxy diluent, the high-temperature thrust, residual adhesive rate and thermal conductivity of the chip are significantly reduced. This is because the epoxy diluent is highly flexible, and the organic phase cross-linking strength of the obtained chip conductive adhesive is insufficient, resulting in poor high-temperature adhesion and poor sintering performance of the silver adhesive.
[0118] (7) It can be seen from Example 1 and Comparative Example 5 that when the formulation does not contain the resin composition, the high-temperature thrust, residual adhesive rate and thermal conductivity of the chip are significantly reduced.
[0119] (8) It can be seen from Example 1 and Comparative Example 6 that when the formula does not contain the resin composition and the epoxy diluent, the high-temperature thrust, residual adhesive rate and thermal conductivity of the chip are significantly reduced.
[0120] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A semi-sintered silver paste, characterized in that: The raw materials for preparing the semi-sintered silver paste include the following components by weight: 35-55 parts of epoxy resin, 20-35 parts of epoxy diluent, 20-40 parts of high temperature resistant resin composition, 1-4 parts of curing agent, 0.2-2 parts of coupling agent, 20-50 parts of inert solvent and 800-900 parts of silver powder; The epoxy diluent includes 1,2-epoxy-4-vinylcyclohexane and / or 3,4-epoxycyclohexyl methacrylate; The high temperature resistant resin composition comprises phenolic resin, bismaleimide and cyanate resin; The mass ratio of the phenolic resin, bismaleimide and cyanate resin in the high-temperature-resistant resin composition is 1:(1-2):(1.5-3).
2. The semi-sintered silver paste according to claim 1, characterized in that: The epoxy resin includes alicyclic epoxy resin; The alicyclic epoxy resin contains at least 2 epoxy groups; The epoxy equivalent of the alicyclic epoxy resin is 100-190 g / Eq.
3. The semi-sintered silver paste according to claim 1, characterized in that: The epoxy equivalent of the phenolic resin is 198-230 g / Eq.
4. The semi-sintered silver paste according to claim 1, characterized in that: The coupling agent includes a silane coupling agent.
5. The semi-sintered silver paste according to claim 1, characterized in that: The curing agent includes an imidazole curing agent and / or an epoxy curing agent.
6. The semi-sintered silver paste according to claim 1, characterized in that: The inert solvent includes any one of diethylene glycol butyl ether, diethylene glycol butyl ether acetate or terpineol, or a combination of at least two of them.
7. The semi-sintered silver paste according to claim 1, characterized in that: The silver powder includes spherical silver powder and / or flaky silver powder; The silver powder is a composition of spherical silver powder and flaky silver powder, and the mass ratio of the spherical silver powder to the flaky silver powder in the composition is 1:(2-4).
8. A method for preparing a semi-sintered silver paste as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing an epoxy resin and a high-temperature-resistant resin composition and heating to dissolve them, then adding an epoxy diluent, a curing agent and a coupling agent, and stirring them evenly to obtain a resin mother solution; (2) adding an inert solvent and silver powder to the resin mother solution obtained in step (1), mixing them evenly, and degassing them under a vacuum environment to obtain the semi-sintered silver paste; The vacuum degree of the vacuum environment is ≤-0.095MPa; The degassing time is 10-25 min.
9. Use of the semi-sintered silver paste according to any one of claims 1 to 8 in packaging of high-power electronic devices.
Citation Information
Patent Citations
High-thermal-conductivity semi-sintered silver colloid as well as preparation method and application thereof
CN118480322A
High-thermal-conductivity nano sintered silver colloid and preparation method thereof
CN115491155A
High-temperature-resistant conductive adhesive and preparation method thereof
CN116496751A